New benzotrithiophene-based molecules as organic P-Type Semiconductor for small-molecule organic solar cells - Castillo, Christian; Aracena Astudillo, Andrés Osvaldo.; Ballesteros, Luis; Neculqueo, Gloria; Gence, Loik; Quero, Franck (MDPI, 2023)
A new benzotrithiophene-based small molecule, namely 2,5,8-Tris[5-(2,2-dicyanovinyl)-2-thienyl]-benzo[1,2-b:3,4-b′:6,5-b″]-trithiophene (DCVT-BTT), was successfully synthesized and subsequently characterized. This compound was found to present an intense absorption band at a wavelength position of ∼544 nm and displayed potentially relevant optoelectronic properties for photovoltaic devices. Theoretical studies demonstrated an interesting behavior of charge transport as electron donor (hole-transporting) active material for heterojunction cells. A preliminary study of small-molecule organic solar cells based on DCVT-BTT (as the P-type organic semiconductor) and phenyl-C61-butyric acid methyl ester (as the N-type organic semiconductor) exhibited a power conversion efficiency of 2.04% at a donor: acceptor weight ratio of 1:1.
Keywords: Benzotrithiophene derivative; Organic solar cells; Small molecule; Semiconductores orgánicos